Theory of Ethics and Ideology - Kuginienė, Lolita (Problemos, 1989)
The article deals with the cognition of morality. It is argued that the cognition depends upon practical presuppositions, namely, values. This in its turn, the argument goes further, produces the conflict between the normative origin of ethics and its scientific character. Further it is claimed that Marxist ethics does not formulate its perspective in such alternative way. It finds scientific way to the problem of values as well to the social presuppositions of ethics. Its starting point for the solution of the problems – the analysis of the needs originating from the alienation nature of social relations.